a/ax + 1 - b/bx +1 = a - b
Answers
Answered by
5
Solution :




{ Dividing both sides by (a - b) }

{ Subtracting 1 from both sides }


Either, x = 0 or, abx + (a + b) = 0
⇒ x = 0, x =
,
which is the required solution.
{ Dividing both sides by (a - b) }
{ Subtracting 1 from both sides }
Either, x = 0 or, abx + (a + b) = 0
⇒ x = 0, x =
which is the required solution.
Similar questions
English,
9 months ago
Social Sciences,
9 months ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago
Economy,
1 year ago
English,
1 year ago
Physics,
1 year ago